Achieving Its Objective: Has the Universal Basic Education Policy Increased the School Enrolment of the Girl Child? - Thomas A. Omang; Dorn C. Enamhe; Mary U. Ojong-Ejoh; Njin O. Egom (EduLine: Journal of Education and Learning Innovation, 2022)
Nigeria has one of the highest numbers of out of school children globally, with the girl child accounting for 60 per cent of this figure. To find a solution to the high number of out-of-school children and the dire state of public-run schools, improve the existing curriculum and educational policy. The Government of Olusegun Obasanjo introduced the Universal Basic Education Policy. The policy objective is to provide nine (9) years of free and compulsory primary and junior secondary education from ages 6 to 15. Adopting the ex-post facto research method, the study examines the impact of the Universal Basic Education policy on school enrollment of the girl child in Calabar South Local Government Area of Cross River State, Nigeria. Data for the study was collected using qualitative and quantitative methods from 390 participants from Calabar South, Cross River State, Nigeria. Data analysis was carried out hypothesis by hypothesis at a 95 per cent confidence level. Data analyzed revealed a significant impact of the Universal Basic Education policy on school enrolments of the girl child. The government should increase and improve its supervisory mechanism in public schools to check for illegal school fees being collected by school management, among others.